Analisis Wacana Kritis Model Teun A. Van Dijk pada Iklan Ramayana Department Store - Fiona Alde Risa; Miftahulkhairah Anwar (Suar Betang, 2021)
Ramayana Department Store advertisement is the advertisement which always visualized before and during Ramadan. Ramayana Department Store ads always shows the unique and impressive ads. One of the Ramayana Department Store advertisement which is mostly watched is “Bahagianya Adalah Bahagiaku”. Around 6.6 million viewers have watched the ads in Youtube channel. The reason is the ads can pull the audiences’s sympathy. The purpose of this research is to show the hidden meaning of the ads by showing its macro structure, super structure and micro structure. This is a descriptive qualitative research with Teun A. van Dijk model approach. The data will be discourses in the form of a dialogue carried out in the ads. The result of this study show that the ads has some elements of macro structure, super structure and micro structure.